Investigating Global Spatial Patterns of Diarrhea-Related Mortality in Children Under Five - Almasi, Ali; Zangeneh, Alireza; Ziapour, Arash; Saeidi, Shahram; Teimouri, Raziyeh; Ahmadi, Tohid; Khezeli, Mehdi; Moradi, Ghobad; Soofi, Moslem; Salimi, Yahya; Rajabi-Gilan, Nader; Ramin Ghasemi, Seyed; et al. (Frontiers in Public Health, 2022)
Objective: Investigating the trends of child diarrhea-related mortality (DRM) has been crucial to track and monitor the progress of prevention and control efforts in world, which requires comprehensive assessment of the levels and trends of child death. This study explores the spatial patterns of diarrhea-related mortality in children under five that is critical for monitoring and designing effective intervention programs. Methods: The data used in this study obtained from the World Health Organization (WHO) public dataset that contains 195 countries data concerning the period of 2000-2017. This dataset contained 13,541,989 DRM cases. The worldwide spatial pattern of DRM was analyzed at the at country level by utilising a Geographic information systems (GIS) software. Moran’s I, Getis-Ord Gi, Mean center and Standard Deviational Ellipse (SDE) techniques were used to conduct the spatial analysis. Results: The spatial pattern of DRM was clustered in all accross the world during the study period of 2000-2017. The results revealed that Asian and African countries had the highest risk worldwide. The findings from the spatial modelling also disclosed that the focal point of death from diarrhea was mainly in Asian countries until 2010, and this focus also shifted to Africa in 2011. Conclusion: DRM is common among children who lived in Asian and African countries. These concentrations may also be due to difference in knowledge, attitude and practices about the diarrheal disease. Through the GIS analysis, the study was able to map the spatial distribution of DRM in temporal and spatial conditions and identify the hotspots of DRM across the globe.